2021
DOI: 10.1007/s10570-021-04034-y
|View full text |Cite
|
Sign up to set email alerts
|

Cellulosic fiber: mechanical fibrillation-morphology-rheology relationships

Abstract: This study aims to investigate the relationship between mechanical brillation, morphological properties, and rheological behavior of cellulosic ber. Three types of cellulosic bers were obtained by adjusting mechanical brillation, namely squashed cellulose, incompletely nano brillated cellulose, and completely nano brillated cellulose, respectively. The squashed cellulose with large size and small aspect ratio had low entanglement capacity, thus forming a weak ber network. The corresponding suspension exhibited… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…Schenker et al (2018) used viscosity and viscoelastic measurements to qualitatively describe the increase in network strength as the degree of fibrillation (DoF) increased in eucalyptus pulp cellulose nanofibres. Yuan et al (2021) also noted the increase in viscosity flow curves as the DoF increased in CNF samples. They qualitatively linked this to increasing aspect ratios, although their reported fibre aspect ratios were determined by AFM and SEM, not the viscosity profiles.…”
Section: Introductionmentioning
confidence: 78%
“…Schenker et al (2018) used viscosity and viscoelastic measurements to qualitatively describe the increase in network strength as the degree of fibrillation (DoF) increased in eucalyptus pulp cellulose nanofibres. Yuan et al (2021) also noted the increase in viscosity flow curves as the DoF increased in CNF samples. They qualitatively linked this to increasing aspect ratios, although their reported fibre aspect ratios were determined by AFM and SEM, not the viscosity profiles.…”
Section: Introductionmentioning
confidence: 78%
“…Generally, MFC suspensions exhibit high viscosities at low shear rates, and a significant shear-thinning behaviour with increasing shear rates, while the viscosity increases, preferably with the fibrils` surface charging rather than with the increasing concentration of MFC (Vesterinen et al 2010;Iotti et al 2011;Karppinen et al 2011;Moberg et al 2017). A transition region (Karppinen et al 2011) and a shear-rate viscosity hysteresis loop effect with a dilatant (non-Newtonian) behaviour at lower shear rates (usually up to 50 s −1 ), has also been reported for most MFC suspensions, already from 1 wt% of solid content (Iotti et al 2011;Yuan et al 2021), thus explaining the shear-induced structural changes of the initial aggregated / flocculated network structure by increasing the shearing. Additional studies (Saarikoski et al 2012;Koponen 2000) also revealed that such a fibrils` flocculation network separates first into chain-like floc formations, and, by further shear rate increase, into individual spherical flocs, the size of which is inversely proportional to the shear rate, and dependent on the geometry gap affecting the measured shear stress.…”
Section: Introductionmentioning
confidence: 63%
“…The study investigates the influences of particle size distribution and interparticle friction coefficient on the solid phase stresses, bulk friction coefficient, and jamming transition, which are investigated. Yuan et al 8 examined the relationship between mechanical fibrillation, morphological properties, and the rheological behavior of cellulosic fibers, considering the winding and interaction of fibers in fiber suspension fluids. Uniform dispersion of fibers in the fracturing fluid enhances the fluid viscosity, which may be called the viscosification of fibers.…”
Section: Introductionmentioning
confidence: 99%